Making Art in the Japanese Way: Nihonga as a Process and Symbolic Action - Gelūnas, Arūnas (Acta Orientalia Vilnensia, 2004)
The aim of the present paper is to show how the school of nihonga is produced institutionally by superimposing features of the traditional paradigm of art-making onto a modern art form in order to “naturalise” it in the Japanese context. It is based on the personal experience of the author as a researcher at the nihonga department of the Tokyo Geijutsu Daigaku (National University of Arts and Music) in 7995-97 and has in part been motivated by the conviction that it is far too early to proclaim the problem of “the distinctive” feel “of Japanese culture” a false problem, that the search for national identity in painting and analyzing “the incompatibility of imported styles and domestic sensibility” is still a point at stake among the Japanese artists and art-critics. This conviction is rather vividly supported by public statements of practicing artists on what the Japanese-style painting is, by the exhibitions focusing on the indigenous elements in Japanese art and by the many hours of communication with nihonga artists and students, especially with the well-known Japanese-style painter Okamura Keizaburo whose creative work is a good testimony to the meaningfulness of the problem raised. As the position of the author of this article was swinging from the critical stare of the outside observer to the empathic participation of nearly an insider; this experience will be treated as a sort of a field-work, though the author was not conscious of his activity as of a kind of “anthropology of art” back then.